2020
DOI: 10.1109/tste.2020.2969292
|View full text |Cite
|
Sign up to set email alerts
|

On the Trade-Off Between Environmental and Economic Objectives in Community Energy Storage Operational Optimization

Abstract: The need to limit climate change has led to policies that aim for the reduction of greenhouse gas emissions. Often, a trade-off exists between reducing emissions and associated costs. In this paper, a multi-objective optimization framework is proposed to determine this trade-off when operating a Community Energy Storage (CES) system in a neighbourhood with high shares of photovoltaic (PV) electricity generation capacity. The Pareto frontier of costs and emissions objectives is established when the CES system w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Researchers have separately studied various aspects of CES integration, such as optimal sizing [21], control [22], [23], techno-economic feasibility [24], [25], etc. Different strategies have been explored for CES management including noncooperative and cooperative game-theory [26], [27], auctionbased models [28], capacity-allocation/capacity-sharing approaches [29], [30], price-based mechanisms [31], multiobjective optimization [32]. The overarching trend of these works is that these studies are generally based on off-line or day-ahead planning of CES operation.…”
Section: Nomenclaturementioning
confidence: 99%
“…Researchers have separately studied various aspects of CES integration, such as optimal sizing [21], control [22], [23], techno-economic feasibility [24], [25], etc. Different strategies have been explored for CES management including noncooperative and cooperative game-theory [26], [27], auctionbased models [28], capacity-allocation/capacity-sharing approaches [29], [30], price-based mechanisms [31], multiobjective optimization [32]. The overarching trend of these works is that these studies are generally based on off-line or day-ahead planning of CES operation.…”
Section: Nomenclaturementioning
confidence: 99%
“…One important aspect that should be highlighted is that most of the previous works that address BESS sizing do not pay attention to the discretization of the BESS variables, i.e., battery and converter capacities. While authors in [33] and [45] use BESS size variables with a level of discretization more compatible with commercial solutions, some works use continuous variables to represent the problem [34], [40], [41], and others use small discretization steps, (e.g., 0.5~1 kWh/kW) [35], [39], [42], [44], [46], [47], which may not be practical and result in high computational complexity.…”
Section: A Literature Review and Research Contributionsmentioning
confidence: 99%
“…However, battery-based energy storage systems can be employed in multi-revenue business models for the provision of multiple services such as market optimization [69], in combination with system balancing [70], and for the provision of peak shaving services in distribution grids [71], compared to simply curtailing the electricity. Furthermore, in this work a pure economic optimization approach is followed, whereas recent work in battery multi-objective optimization, by considering both economic and environmental objectives, has shown that costs and emissions can simultaneously be decreased [72]. Therefore, it is recommended that future research also considers the utilization of battery-based storage systems for multiple purposes in increasing its value, as well as the use of second-life Li-ion batteries from electric vehicles.…”
Section: Battery Systemmentioning
confidence: 99%